2009
DOI: 10.1016/j.annepidem.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Employment Status, Coronary Heart Disease, and Stroke Among Women

Abstract: Purpose To investigate the association of employment status with CHD and ischemic stroke among middle-aged women. Methods Proportional hazards regression was used to assess the association of employment status, incident CHD, and incident ischemic stroke among 7,058 women, aged 45-64 years at baseline (1987-89), from the Atherosclerosis Risk in Communities Study. Results After adjusting for age and race-field center, women employed outside the home had a decreased risk of CHD (hazard ratio (HR) =0.70, 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
4
10
1
7
Order By: Relevance
“…Employment was associated with a 61-76% reduction in the prevalence of stroke across all ages. As a recent study suggested, employed women were at a lower risk of developing ischemic stroke [32]. Our finding is probably due to the fact that employed people are more likely to have higher education, insurance coverage and healthy behaviors that may be protective against stroke.…”
Section: Discussionsupporting
confidence: 52%
“…Employment was associated with a 61-76% reduction in the prevalence of stroke across all ages. As a recent study suggested, employed women were at a lower risk of developing ischemic stroke [32]. Our finding is probably due to the fact that employed people are more likely to have higher education, insurance coverage and healthy behaviors that may be protective against stroke.…”
Section: Discussionsupporting
confidence: 52%
“…В первую очередь, профессиональная занятость является одним из факторов исходного состояния здоровья пациента с ИМ. Многочисленные литературные данные свиде-тельствуют о более лучшем состоянии здоровья в целоми, в частности, сердечно-сосудистом здоровье у работаю-щей популяции [5,7,9]. В основе данных результатов находится понятие "эффекта здорового рабочего", заключающегося в искус ственном и стихийном устране-нии больных и ослабленных лиц из трудового процесса [10].…”
Section: Discussionunclassified
“…В то же время, исследований, посвященных непо-средственной оценке зависимости сердечно-сосудис-той патологии или смертности от трудовой занятости, довольно немного: ряд современных исследований сви-детельствуют о более высоком риске артериальной гипертонии [6], ишемической болезни сердца, ишеми-ческого инсульта [7], а также смертности от сердечно-сосудистых заболеваний [8] у неработающего населения в трудоспособном возрасте.…”
unclassified
“…У работающих в возрасте 45-64 лет ниже риск развития ИБС (отношение шансов OR=0,70 при 95% ДИ 0,56-0,86) и ишемического инсульта (OR=0,62 при 95% ДИ 0,47-0,84) [12], АГ (OR=0,70 при 95% ДИ 0,62-0,79), ниже уровень ОХС и глю-козы. Среди работающих женщин выше уровень хо-лестерина ЛПВП, чем среди не работающих (даже после поправки на возможные модифицирующие факторы: массу тела, курение, физическую актив-ность и др.)…”
Section: оригинальные статьиunclassified
“…Среди работающих женщин выше уровень хо-лестерина ЛПВП, чем среди не работающих (даже после поправки на возможные модифицирующие факторы: массу тела, курение, физическую актив-ность и др.) [12]. У женщин, уходящих из трудовой деятельности, уровень холестерина ЛПВП снижал-ся, что авторы связывают с изменением образа жиз-ни, в первую очередь, с питанием, употреблением алкоголя и беременностью.…”
Section: оригинальные статьиunclassified